Effect of paste viscosity on direct-current resistance in improving the efficiency of dye-sensitized solar cell - Zaine, S.N.A. (Universiti Teknikal Malaysia Melaka, 2018)
The quality of photoelectrode film plays an important role in producing high performing dye-sensitized solar cell (DSC). A well-deposited film would ensure the stability of photoelectrode material and improve electron transport and recombination. This study aims to evaluate the effect of paste viscosity on the direct-current resistance of the fabricated DSC. Photoelectrode paste of different viscosity was prepared by varying the amount of terpineol as the solvent. Photoelectrode films were then deposited on fluorine-doped tin oxide glass substrate by screen printing method. Electrochemical impedance spectroscopy analysis was utilized to analyse the direct-current resistance of fabricated DSC integrated with different paste viscosity. Direct-current resistance is found to be reduced with increasing paste viscosity. This is attributed to the increase in electron density which reduces the transport as well as recombination resistance leading to an improvement in the conversion efficiency. Â© 2018 Universiti Teknikal Malaysia Melaka. All rights reserved.